The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1093/mnras/sty2173
|View full text |Cite
|
Sign up to set email alerts
|

X-ray Intraday Variability of the TeV Blazar Mrk 421 with Chandra

Abstract: We present an extensive study of 72 archival Chandra light curves of the highfrequency-peaked type blazar Mrk 421, the first strong extragalactic object to be detected at TeV energies. Between 2000 and 2015 Mrk 421 often displayed intraday variability in the 0.3-10.0 keV energy range, as quantified through fractional variability amplitudes that range up to 21.3 per cent. A variability duty cycle of ∼ 84 per cent is present in these data. Variability timescales, with values ranging from 5.5 to 30.5 ks, appear t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
23
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 91 publications
5
23
0
Order By: Relevance
“…We found that for observations on MJD 56,420 and MJD 56,486, the HR increases with increasing flux, that is, the NuSTAR spectra of Mrk 501 became harder with the increasing count rates. Such a "harder-when-brighter" trend has often been noticed in X-ray observations of the HBL-type blazars (e.g., [19,42,43], and references therein). For the other five observations, no strong correlation were seen between HR and count rates.…”
Section: Summary and Discussionmentioning
confidence: 55%
“…We found that for observations on MJD 56,420 and MJD 56,486, the HR increases with increasing flux, that is, the NuSTAR spectra of Mrk 501 became harder with the increasing count rates. Such a "harder-when-brighter" trend has often been noticed in X-ray observations of the HBL-type blazars (e.g., [19,42,43], and references therein). For the other five observations, no strong correlation were seen between HR and count rates.…”
Section: Summary and Discussionmentioning
confidence: 55%
“…Hard and soft bands were well correlated with zero time lag, and in general harder-when-brighter trend in the spectral behavior was found [31,60]. In hardness ratio (HR) versus X-ray flux plots, we noticed a clockwise as well as anti-clockwise loop at different epochs of observations which implied that particle acceleration as well as synchrotron cooling both work in the source at different epochs of observations [60]. In a systematic study of the 16 year whole operation period of RXTE, 32 TeV blazar spectra were analyzed.…”
Section: Flux and Spectral Variabilitymentioning
confidence: 78%
“…IDV timescales ranging 2.4-30.0 ks, IDV duty cycle ∼77%, soft (0.3-2.0 keV) and hard (2.0-10.0 keV) LCs well correlated with zero lag were found. IDV timescales were also used to calculate δ the Doppler factor, B the magnetic field, γ the Lorentz factor and R the size of emitting region for the blazar Mrk 421 [43]. For Mrk 421, we found that shortest IDV timescale ≈2.…”
Section: Idv In X-raysmentioning
confidence: 87%
“…A pilot project on searching for IDV in blazars was initiated ( [28,37,42,43,54]; and the references therein). A sample of four HBLs observed on 23 occasions by XMM-Newton was studied; IDV timescales ranging from 15.7-46.8 ks were found on eight occasions; in 13 cases, IDV timescales were longer than the data length, and the hint of weak quasi periodic oscillations (QPOs) was observed on one LC each of blazars ON 231 and PKS 2155-304 [28].…”
Section: Idv In X-raysmentioning
confidence: 99%
See 1 more Smart Citation